STABILITY ANALYSIS OF SLOPES USING A DOUBLE SLIDING MODEL - Mohammed Yousif Fattah (Journal of Engineering, 2003)
Experience with Bishop's method, using the shear strength parameters c and obtained fron triaxial compression tests seems to indicate that the values of the safety factor obtained in this way are relatively large. This is sometimes compensated by using shear strength parameters obtained from direct shear tests, simple shear tests, or classical cell tests, which usually lead to smaller values of c and . A solution for the difficulty mentioned above may be the notion that the simple Coulomb formula does not take into account that failure may occur on a plane perpendicular to the global slip surface, with an additional rotation to result in global slip parallel to the slip surface, i.e. double sliding failure model.The essential step in developing the basic formula for many slope stability methods (Fellenius, Bishop, Janbu) is to derive an expression for the normal stress on the slip surface. In the Bishop method this is done by combining the equation of vertical equilibrium in which it is assumed that there is no net contribution of the shear forces on the sides of the slice, with the Coulomb equation.The alternative mechanism proposed is that failure occurs not hecause the shear stress on the slip surface reaches the maximum value described by the Coulomb criterion, but that the shear stress on a plane perpendicular to the slip surface (and thus also the shear stress on a plane parallel to the sl.p surface) reaches the maximum vales on this perpendicular plane, and thus, using a safety factor F In this paper, a comparison is made of the factor of safety calculated by the double sliding model with those calculated by Fellenius and Bishop's methods.